Digital transformation in tourism and hospitality : sustainable management strategies for long-term excellence - Dana, Léo-Paul; Kumar, Anuj; Gupta, Vijay Prakash (Emerald Publishing Limited, 2025)
In the era of a constantly changing tourism and hospitality landscape, Digital Transformation in Tourism and Hospitality: Sustainable Management Strategies for Long-Term Excellence serves as a comprehensive guide on how to lead, innovate, and sustain forward-thinking approaches within the industry. Catering to leaders, entrepreneurs, and academics, it distils ground-breaking ideas about the impact of digital innovations and how sustainability-centric practices are shaping the future of travel. Explore how emerging technologies--such as artificial intelligence, data analytics, and digital marketing--can be leveraged to create seamless, immersive guest experiences while addressing critical environmental and social challenges. Digital Transformation in Tourism and Hospitality is a roadmap to future-proof leadership, filled with case studies, expert insights, and actionable frameworks. From implementing green technology to optimizing digital operations, each chapter provides a deeper understanding of how to achieve sustainable success in an industry where environmental and social responsibility are essential for differentiation and resilience. Whether you are a tourism professional, business strategist, or academic, this book equips you to drive responsible growth and achieve long-term excellence in a digitally driven world.